The Effect of Surface Acting on Job Stress and Cognitive Weariness Among Healthcare Workers During the COVID-19 Pandemic: Exploring the Role of Sense of Community - Sousan, Arman; Farmanesh, Panteha; Zargar, Pouya (Frontiers in Psychology, 2022)
Surface acting (SA) is a heavy emotional and cognitive task practiced by nurses, which has negative consequences on their wellbeing. The shortage of nurses along with the occurrence of the COVID-19 pandemic has worsened the situation. Based on job demands-resources (JD-R) and conservation of resources theories, this study aims to investigate the adverse impact of practicing SA and buffering effect of a sense of community (SOC) on job stress (JS) and cognitive weariness (CW) among Iranian nurses confronting COVID-19. As this study is written within the scope of Frontiers’ call for research on “Spirituality in the workplace,” the findings suggest that the aforementioned factors are in significant positive relationships. Furthermore, the empirical evidence indicates that there is a significant indirect effect of SA on CW through JS. In addition, results reveal that there is a buffering effect of SOC on the SA and JS relationship, while there is no significant moderation effect regarding the JS and cognitive weariness association. The findings of this study provide theoretical and practical implications within the scope of spirituality in the workplace.